2020
DOI: 10.34172/jcs.2020.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Programmed Family Presence in Coronary Care Units on Patients’ and Families’ Anxiety

Abstract: Introduction: Hospitalization of patients in the intensive care units always has negative consequences such as anxiety and concern for patients and their families. This study aimed to investigate the effect of programmed family presence in intensive care units on patients’ and families’ anxiety. Methods: This was a quasi-experimental study conducted in Iran. The eligible patients and a member of their families were assigned into two groups (N = 80) through convenience sampling. The family members in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Restricted ICU visiting policies outside of a pandemic influence the psychological well-being of family members more than they influence ICU patients, as family members experience distress and anxiety because of being kept from the bedside ( 10 ). The absence of family members at the ICU bedside has a negative impact on patient recovery and psychological outcomes ( 11 , 12 ). Family absence also negatively influences information transfer and has the potential to reduce the understanding of patient wishes, past medical history, and current care history, with family members often being the best keepers of continuity-of-care information.…”
mentioning
confidence: 99%
“…Restricted ICU visiting policies outside of a pandemic influence the psychological well-being of family members more than they influence ICU patients, as family members experience distress and anxiety because of being kept from the bedside ( 10 ). The absence of family members at the ICU bedside has a negative impact on patient recovery and psychological outcomes ( 11 , 12 ). Family absence also negatively influences information transfer and has the potential to reduce the understanding of patient wishes, past medical history, and current care history, with family members often being the best keepers of continuity-of-care information.…”
mentioning
confidence: 99%
“…The interruption of music during the intervention may negatively affect achievement of the expected benefits. During the delivery of music interventions, even the presence of family members should be carefully evaluated, as there is no consensus in the literature as to the effect of the presence of family members or significant o on symptom management [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study found that there was a significant decrease in anxiety levels in all patients under IMV, non‐IMV, and simple mask/HFNC support after sVPVs; this decrease was higher in patients under simple mask/HFNC and non‐IMV support when compared to patients under IMV support. Studies conducted prior to the COVID‐19 pandemic showed that the majority of patients (12%–60%) admitted to the ICU experience moderate to severe anxiety due to factors such as being in a foreign environment, severity of the disease, isolation from their families, and risk of death (Kamali et al, 2020; Shdaifat et al, 2020). Patient visit restrictions prevent weaning from mechanical ventilation, compliance with the treatment process, and motivation, especially in intubated patients (Rose et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in order to understand the patient's experience in the ICU, encourage effective decision‐making, and prepare for recovery after discharge, it is essential that patients' relatives maintain regular communication with patients (Valley et al, 2020). Research shows that patients' access to their family members leads to a sense of calmness in patients and has a positive effect on reducing the use of sedative agents, cognitive impairment, anxiety, confusion, agitation and delirium in patients (Fumis et al, 2015; Kamali et al, 2020; Wong et al, 2018). Family members' ability to communicate with unconscious patients at every stage of the intensive care process, even virtual, eliminates the sense of abandonment, provides social support and eases their psychological burden, despite the feelings of isolation and loneliness.…”
Section: Discussionmentioning
confidence: 99%